2022
DOI: 10.1111/ene.15483
|View full text |Cite
|
Sign up to set email alerts
|

Structural magnetic resonance imaging in dystonia: A systematic review of methodological approaches and findings

Abstract: Background and purpose: Structural magnetic resonance techniques have been widely applied in neurological disorders to better understand tissue changes, probing characteristics such as volume, iron deposition and diffusion. Dystonia is a hyperkinetic movement disorder, resulting in abnormal postures and pain. Its pathophysiology is poorly understood, with normal routine clinical imaging in idiopathic forms. More advanced tools provide an opportunity to identify smaller scale structural changes which may underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…In line with our findings, recent studies applying diffusion tensor imaging (DTI), which is an MRI-based axonal injury imaging marker that enables in vivo mapping of the diffusion of water molecules in brains to characterize changes in white matter integrity specific to axons [26], demonstrated that patients with idiopathic adult-onset focal dystonia have significantly reduced fractional anisotropy in the basal ganglia and cerebellum compared to controls, suggesting a process of axonal loss [27,28]. A recent study reviewing 1945 participants with dystonia undergoing DTI revealed fewer cerebello-thalamic tractography streamlines in genetic forms of dystonia than in idiopathic dystonia, suggesting more profound microstructural brain changes in those diagnosed with genetic dystonia [29]. However, few DTI-based studies have been performed in patients with generalized dystonia or combined dystonia syndrome due to its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, recent studies applying diffusion tensor imaging (DTI), which is an MRI-based axonal injury imaging marker that enables in vivo mapping of the diffusion of water molecules in brains to characterize changes in white matter integrity specific to axons [26], demonstrated that patients with idiopathic adult-onset focal dystonia have significantly reduced fractional anisotropy in the basal ganglia and cerebellum compared to controls, suggesting a process of axonal loss [27,28]. A recent study reviewing 1945 participants with dystonia undergoing DTI revealed fewer cerebello-thalamic tractography streamlines in genetic forms of dystonia than in idiopathic dystonia, suggesting more profound microstructural brain changes in those diagnosed with genetic dystonia [29]. However, few DTI-based studies have been performed in patients with generalized dystonia or combined dystonia syndrome due to its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…White matter analysis in AOIFCD has predominantly involved diffusion MRI, using relatively non-specific measures, coupled with heterogenous approaches and findings. Some have demonstrated localised higher, lower or unchanged diffusion tensor measures such as fractional anisotropy (FA) and mean diffusivity (MD) within motor pathways (5,(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric MRI has indicated higher volumes in task-specific forms of dystonia, most notably in the cerebellar, basal ganglia and sensorimotor grey matter regions [ 34 ], with variable findings in non-task-specific forms. Findings from diffusion MRI (dMRI) studies have been mixed, although cerebellar white matter projections, and white matter deep to the primary sensorimotor cortices have been highlighted [ 23 ]. There is also evidence for genotypic and phenotypic variation, including more widespread changes in genetic dystonias and intermediate changes in non-motor manifesting gene carriers.…”
Section: Introductionmentioning
confidence: 99%